An Analysis Lexical Cohesion In Jakarta Post News - Muhammad Hasyimsyah Batubara; Cut Dara Ilfa Rahila; Ridaini Ridaini (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
This research is about lexical cohesion (repetition, synonym, antonym, hyponym, collocation). This study's objectives were: (1) to find the type of LC in the reportage, and opinion column of Jakarta Post News and (2) find the dominant type of LC in the reportage and opinion column of Jakarta Post News. Researchers used library research, while the data sources were the news reports and opinion texts of the Jakarta Post News, which consisted of 30 opinion news and 30 reportage news in edition October. Data analysis used Miles and Huberman's model (reduction, display and verification). The results found synonym 94, repetition 87, antonym 67, hyponym 40, collocation 30. The total LC in the Jakarta Post News is 318. The dominant LC in the Jakarta Post is synonymous with a total of 94 words.